Management of Colles' Fracture by Conservative VS Open Reduction Bone Grafting and Internal Fixation with K-Wire - Khan, Javed Ahmad; Mahara, D. P. (Journal of Nepal Health Research Council, 2009)
Not uploaded. Key words: Fracture; Open reduction; Bone grafting; Close reduction. DOI: 10.3126/jnhrc.v6i1.2439 Journal of Nepal Health Research Council Vol. 6, No. 1, Issue 12, April, 2008 Page: 16-21